2017
DOI: 10.7326/m17-0537
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Glycemic Control for U.S. Adults With Type 2 Diabetes

Abstract: Background Intensive glycemic control in type 2 diabetes (glycated hemoglobin [HbA1c] level <7%) is an established, cost-effective standard of care. However, guidelines recommend individualizing goals on the basis of age, comorbidity, diabetes duration, and complications. Objective To estimate the cost-effectiveness of individualized control versus uniform intensive control (HbA1c level <7%) for the U.S. population with type 2 diabetes. Design Patient-level Monte Carlo–based Markov model. Data Sources Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 58 publications
1
29
0
1
Order By: Relevance
“…These utility changes were similarly applied to CV outcomes in the GCK-MODY model. Utility changes associated with complications for type 2 diabetes patients were similar to those reported elsewhere (25).…”
Section: Quality Of Life Effectssupporting
confidence: 84%
“…These utility changes were similarly applied to CV outcomes in the GCK-MODY model. Utility changes associated with complications for type 2 diabetes patients were similar to those reported elsewhere (25).…”
Section: Quality Of Life Effectssupporting
confidence: 84%
“…Our study thus highlights the need for personalizing treatment targets in adults with type 2 diabetes and implementing diabetes quality improvement strategies [ 41 ] that are flexible enough to focus on both the potential over-treatment of multimorbid patients as well as potential under-treatment of healthier patients and to consider both blood pressure as well as glycemic targets. To that end, it is worth noting that a recent Monte Carlo-based Markov Model decision analysis confirmed that care to achieve individualized treatment targets was cost-saving and associated with a small improvement in quality of life [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For people with type 2 diabetes, we modelled lifetime outcomes using the U.S. Type 2 Diabetes Policy Model [22][23][24], an individual population-level, Monte Carlo-based Markov model ( Fig. 1) (see Appendix S1 for details).…”
Section: Simulation Modelsmentioning
confidence: 99%